2014
DOI: 10.1016/j.mito.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

The mitochondrial respiratory chain of the secondary green alga Euglena gracilis shares many additional subunits with parasitic Trypanosomatidae

Abstract: The mitochondrion is an essential organelle for the production of cellular ATP in most eukaryotic cells. It is extensively studied, including in parasitic organisms such as trypanosomes, as a potential therapeutic target. Recently, numerous additional subunits of the respiratory-chain complexes have been described in Trypanosoma brucei and Trypanosoma cruzi. Since these subunits had apparently no counterparts in other organisms, they were interpreted as potentially associated with the parasitic trypanosome lif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
109
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(124 citation statements)
references
References 90 publications
12
109
3
Order By: Relevance
“…This unusual arrangement of catalytic subunits is surprising, given the otherwise strictly conserved pseudo-sixfold symmetry and catalytic mechanism of the (αβ) 3 hexamer in all other known F-type ATPases, including those of bacteria and chloroplasts (4,24,40). The observed alterations in the T. brucei and E. gracilis F 1 region are in line with previous biochemical studies reporting a complete cleavage of the α subunit into two fragments, both of which remain bound to the ATP synthase (10)(11)(12)(13)(14). Furthermore, it has been shown that despite the α-subunit fragmentation, the T. brucei ATP synthase remains catalytically active throughout the life cycle and is essential for parasite survival in both the procyclic and bloodstream forms (10,16,18,19); as mentioned above, it is the reverse function as a proton-pumping ATPase that is essential for survival in the mammalian host.…”
Section: Dimer Rows In Euglena and Trypanosomes Indicate An Unexpectedsupporting
confidence: 83%
See 3 more Smart Citations
“…This unusual arrangement of catalytic subunits is surprising, given the otherwise strictly conserved pseudo-sixfold symmetry and catalytic mechanism of the (αβ) 3 hexamer in all other known F-type ATPases, including those of bacteria and chloroplasts (4,24,40). The observed alterations in the T. brucei and E. gracilis F 1 region are in line with previous biochemical studies reporting a complete cleavage of the α subunit into two fragments, both of which remain bound to the ATP synthase (10)(11)(12)(13)(14). Furthermore, it has been shown that despite the α-subunit fragmentation, the T. brucei ATP synthase remains catalytically active throughout the life cycle and is essential for parasite survival in both the procyclic and bloodstream forms (10,16,18,19); as mentioned above, it is the reverse function as a proton-pumping ATPase that is essential for survival in the mammalian host.…”
Section: Dimer Rows In Euglena and Trypanosomes Indicate An Unexpectedsupporting
confidence: 83%
“…In contrast, there seem to be no subunits in the protozoan-type ATP synthases that correspond to the peripheral stalk or dimer interface in the metazoan type. Instead, proteomics and biochemical analysis have identified several unique subunits, none of which are homologous among the various phyla (10,11,36,37). This variation in subunit composition correlates with the observed diversity in structure, which may reflect adaptations to different energetic requirements or environmental conditions.…”
Section: Dimer Rows In Euglena and Trypanosomes Indicate An Unexpectedmentioning
confidence: 98%
See 2 more Smart Citations
“…However, recent work with bovine mitochondria elegantly suggests that there is just one common pool of ubiquinone/ubiquinol and cytochrome c, which is free to interact with any OXPHOS components found in the protein-dense mt inner membrane (60). Whereas the interactions between respiratory supercomplexes appear to be quite delicate, the detection of the dimeric F o F 1 -ATP synthase has been more pervasive throughout the eukaryotic supergroups studied so far, including the protists of the supergroups Excavata and Alveolata (T. brucei, Euglena gracilis, Plasmodium falciparum, and Tetrahymena thermophila) (13,(61)(62)(63)(64). This dimerization is proposed to be crucial for crista formation within the mt inner membrane (65), and the commonality of this structural organization in a wide variety of eukaryotes suggests that it was an early attempt to create microenvironments for components of the OXPHOS pathway.…”
Section: Discussionmentioning
confidence: 99%